Acceptance of internet banking in Pakistan: integration of unified theory of acceptance and use of technology and DeLone and McLean IS model: Acceptance of internet banking in Pakistan: integration of unified theory of acceptance and use of technology and DeLone and McLean IS model (KASBIT Business Journal, 2022)
This study explored the reasons impacting the continuation usage intent towards internet banking in Pakistan. In developing countries, internet banking is comparatively a new phenomenon. Hence it is imperative to find out elements influencing the persistent usage intention of banking customers. This research integrated DeLone and McLean's information system success model with a unified theory of acceptance and usage of technology to find out the factors contributing to satisfaction of customers and continuance usage intention. SEM was utilized for the analysis. The results explained 69% of the variance in continuance usage intention to adopt internet banking in Pakistan.